Rainfall Prediction Due to the Madden Julian Oscillation Factor at the Equator - Firda Kusfirdianti; Joko Wiratmo (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
In this research, the process of spectral analysis (Fast Fourier Transform) was carried out as a step to find out the phenomena that affect rainfall in the equatorial region which are represented by the cities of Kototabang, Pontianak, Gorontalo and Biak. This is followed by predicting rainfall due to the MJO phenomenon, which is obtained after performing a Bandpass Filter with a cut off of 30 and 90 days on rainfall time series data and the Inverse Fast Fourier Transform (IFFT), using the ARIMA method. The results showed that the study area under study generally had an equatorial rainfall pattern type. This rainfall is dominantly influenced by annual (monsoon) and semi-annual (ITCZ) phenomena. There is an intra-seasonal phenomenon (MJO) although it does not have a big impact on rainfall. ARIMA provides fairly good rainfall prediction results for a short period of time. Monthly rainfall predictions show values ​​below 90 mm, with the lowest predicted rainfall occurring in January in Gorontalo (42.57 mm), and the highest in February in Biak (86.83 mm).